#### Answer

$$ y =\frac{6}{x^2}$$

#### Work Step by Step

Given $$ x=e^{-2t},\ \ \ \ y= 6e^{4t}$$
Since $ e^{2t}=\frac{1}{x}$, then
\begin{align*}
y&= 6e^{4t}\\
&= 6(e^{2t})^2\\
&=\frac{6}{x^2}
\end{align*}
i.e.
$$ y =\frac{6}{x^2}$$

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$ y =\frac{6}{x^2}$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.